Pengaruh Literasi Keuanga, Pendapatan, Status Pernikahan dan Haya Hidup Terhadap Perilaku Berhutang - Erin Soleha; Zulfa Zakiatul Hidayah (REVITALISASI : Jurnal Ilmu Manajemen, 2023)
Debt behavior nowadays is a common thing for someone to do, from small children, adults to the elderly, they must have carried out debt and credit activities. People often use debt as an alternative to getting funds when they are pressed or when their finances are inadequate. This study aims to prove the relationship between Financial Literacy, Income, Marital Status, and Lifestyle that influence Debt Behavior. This study uses a quantitative approach using primary data from 99 respondents with a questionnaire as a data collection tool. The sample used in this study is the people of West Java Province with the Accidental Sampling method. The analytical method used to analyze the data is Partial Least Square with the outer model and inner model coefficient tests with the help of Smart PLS software. The results showed that financial literacy and income had an effect on debt behavior while marital status and lifestyle had no effect.